Welcoming The Opportunities: Deciphering Contemporary Mobility of Indonesian Professionals to Japan - Firman Budianto (Intermestic: Journal of International Studies, 2023)
The research on how transnational mobility of professionals from developing countries is facilitated and constructed are still developing. Drawn on qualitative data from in-depth interviews with Indonesian professionals in Japan between 2018 and 2020 as a case study, this article discusses all the factors that facilitate the mobility of Indonesian professionals to Japan, including the individual narratives related to both Indonesia and Japan. The case study of Indonesian professionals in Japan demonstrates that the intersections of not only credentials, skills, and transnational economy between Japan and Indonesia, but also the various emerging channels such as scholarship regimes and the changing in Japan’s domestic labor market and recruitment systems have created a set of opportunities that increasingly pave the way for foreign professionals to build a career in Japan while contributing to the homeland. The transnational mobility of working professionals from developing countries to Japan could be seen as a form of welcoming such opportunities and it makes working in Japan as one of the options global talents can choose